2012
DOI: 10.1590/s0103-64402012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd:YAG laser combined with fluoride on the prevention of primary tooth enamel demineralization

Abstract: Most studies dealing with the caries preventive action of Nd:YAG laser have been done in permanent teeth and studies on primary teeth are still lacking. The aim of this study was to evaluate in vitro the effect of Nd:YAG laser combined or not with fluoride sources on the acid resistance of primary tooth enamel after artificial caries induction by assessing longitudinal microhardness and demineralization depth. Sixty enamel blocks obtained from the buccal/lingual surface of exfoliated human primary molars were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
21

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 19 publications
0
30
0
21
Order By: Relevance
“…Irradiation of dental enamel with high power lasers has shown to be effective in preventing dental caries, because they can provide significant reduction in mineral loss by the acid challenges in the oral cavity (1,2). Different hypotheses have been proposed to explain the changes promoted by irradiation in dental enamel resulting in a preventive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of dental enamel with high power lasers has shown to be effective in preventing dental caries, because they can provide significant reduction in mineral loss by the acid challenges in the oral cavity (1,2). Different hypotheses have been proposed to explain the changes promoted by irradiation in dental enamel resulting in a preventive effect.…”
Section: Introductionmentioning
confidence: 99%
“…In most previous studies, WSLs were not present on the teeth surfaces in the first place and incipient caries were later induced artificially via demineralization and remineralization cycles. [11][12][13]18,20,21,30,33 The current study results showed that in the nointervention control group, where the samples were only immersed in artificial saliva, no change occurred …”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the samples were initially sound and were then subjected to demineralization/ remineralization cycles. 33 Tagliaferro et al assessed primary enamel resistance to demineralization by the Knoop microhardness test. The enamel resistance in groups treated with laser and/or APF was higher compared to the control group, and combined application of laser and fluoride caused no significant change in the results compared to other interventions, which is similar to the current study results.…”
Section: G1 G2 G3mentioning
confidence: 99%
“…There are studies which were performed on the synergistic effect of laser irradiation and fluoride or other remineralizing agents on remineralization (23,24). Most of these studies have been conducted on permanent teeth and have primarily assessed mineral loss, fluoride content and surface topography of enamel following laser irradiation.…”
mentioning
confidence: 99%